(3CSGS GdJChjd GdHGWfs - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s ((3fGUQ Hf MSf s)
(3ChdgG (B:s
(3GdMeO ddg eajO GdfYeI GeG HYO aEfG HJCjjO Gddg hGeJfGfg hYhfg haVdg hEMSGfg cfG bO HSWfG ddeSJLjHjf s
(3BNQgG (B:s
(3hEf YdjfG UdhGJ Gddg Ydjg OYG gePGf aCLGHg efge eGFI QLd Ydjge GdOQhY s
(3fSNI CNQi efbU ef GdJUhjQ hQbI Qbe (B129s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B106s
Keywords: (3eJaQbGJs